Інтерпретація авторського «Я» крізь призму епістолярного дискурсу Ольги Кобилянської : (до 160-річчя від дня народження) - Kosmeda, Tetyana; Papish, Vitaliia (Theoria et Historia Scientiarum, 2024)
The paper highlights the postulates of personal discourse theories (egotext) designed for the aspectual clarification of Olha Kobylianska’s epistolary discourse originality. The strokes of the writer’s biography are analyzed via the prism of her self-awareness concerning individual preferences, passions, and aspirations, in particular with an indication of the incomplete life potential realization (loneliness is critically evaluated), the presentation of the philosopher’s key worldviews, primarily feminist (gender) beliefs, and the understanding of her own creative potential national-genetic basics. It is demonstrated how O. Kobylianska expresses her views on the environment, religion, mysticism, psychology, and shows her love for learning and mastering Polish and German as foreign languages; her artistic writing in general, the tendency to intuitive prediction reflections, and her interest in music and theater are also discussed in the piece of research. The artist sincerely admits that her emotions are not always controlled during the creative process, as well as in real-life situations. In the writer’s epistolary thesaurus, one can trace the vocabulary and phraseology frequency to indicate certain psychological states and emotions, which proves that in O. Kobylianska’s nature are high sensuality, emotionality, and expressiveness. The artist’s epistolary behavior features (politeness, self-irony, humorous tone, benevolence and emotionality) display her epistolary idiostyle originality, indicating a distinct soul sensitivity. The lexeme soul has a high frequency in the text of the considered letters and presents powerful semantic and pragmatic content. O. Kobylianska’s letters analysis makes it possible to claim that she is a talented writer, an introverted type of thinking individual, a born psychologist, as well as a connoisseur of Ukrainian and other linguistic cultures.